The Factors Associated with The Incidence of Scabies Among Students - Amelia Yunita Wardhani; Sitti Badrah; Ayudhia Rachmawati; Syamsir Syamsir; Akhmad Azmiardi (Poltekkes Kemenkes Semarang, 2026)
Scabies is a skin infection caused by tiny mites that burrow into the skin, resulting in intense itching and rashes. This issue is common in developing countries and significantly contributes to skin disorders. Islamic boarding schools (pondok pesantren) are among the locations where scabies outbreaks occur, and various factors influence their incidence. This study aims to identify the factors associated with the occurrence of scabies among students at Al-Khairaat Islamic Boarding School in Tideng Pale Village, Tana Tidung District, in 2025. This research employs a quantitative analytical observational approach with a cross-sectional design. Data are analyzed univariately and followed by bivariate analysis using the chi-square test to identify significant relationships. The results indicate that the variable of clothing hygiene (p = 0.046; OR = 4.000) has a significant association with the incidence of scabies. On the other hand, knowledge (p = 1.000; OR = 1.031), housing density (p = 0.616; OR = 0.654), bed hygiene (p = 0.593; OR = 1.684), towel hygiene (p = 0.375; OR = 1.860), and bathing hygiene (p = 0.587; OR = 1.643) were not significantly associated with scabies incidence. The incidence of scabies at Al-Khairaat Islamic Boarding School is associated with clothing hygiene. Therefore, efforts to improve personal and environmental hygiene through education, sanitation facility improvements, and collaboration between the boarding school, community health centers, and the Health Office are essential to prevent and control scabies sustainably.